Antimicrobial Susceptibility Testing to Erythromycin and Azithromycin of Clinical Isolates of Bordetella pertussis Circulating in Russia - A. S. Pimenova; N. T. Gadua; I. Yu. Andrievskaya; O. Yu. Borisova; M. S. Petrova; A. B. Borisova; S. S. Afanas'ev; I. V. Podoprigora; M. S. Afanas'ev; T. I. Moskvina; G. V. Vorob'eva; I. M. Degtyareva; et al. (Эпидемиология и вакцинопрофилактика, 2024)
Relevance. Antibacterial drugs are widely used to treat and prevent infections of the upper and lower respiratory tract. The large-scale and unjustified use of antimicrobials to treat these infections has led to the emergence of resistance in most pathogens. The aim. To study antimicrobial susceptibility testing to erythromycin and azithromycin of strains of B. pertussis isolated in Russia. Materials & Methods. The research included 165 strains of B. pertussis isolated in January 2014 to June 2020. Antimicrobial susceptibility to erythromycin and azithromycin was determined by disk diffusion method and MIC test (HiMedia Laboratories Pvt. Limited, India). The A2047G mutation in the 23S rRNA gene was detected by PCR and subsequent sequencing. Results. Disk diffusion zone diameters for erythromycin in the studied strains ranged from 25 to 62 mm (median 44 mm) and disk diffusion zone diameters for azithromycin ranged from 22 to 80 mm (median 50 mm). Isolates with growth inhibition of more than 42 mm in diameter after 7 days of incubation were considered as susceptible. Among the studied strains, 57 (34.5%) were resistant to erythromycin and 23 (13.9%) to azithromycin. Then, MIC of erythromycin and MIC of azithromycin, respectively, were determined for these 57 and 23 strains using the MIC test. The comparison group included 79 isolates that were classified as sensitive to erythromycin (n = 31) and azithromycin (n=48) according to the results of the previous study. A MIC value of 0.12 μg/ml was considered as the cut-off for susceptible strains. All isolates were fully susceptible to erythromycin (MIC ≤ 0.01 μg/ml, median MIC 0.001 μg/ml) and azithromycin (MIC ≤ 0.01 μg/ml, median MIC 0.0001 μg/ml). An A-to-G mutation was not found at position 2047 in the 23S rRNA gene in 80 isolates that had a diameter of growth inhibition zone less than 42 mm. Conclusion. This study demonstrates no significant decrease in the susceptibility to erythromycin and azithromycin among B. pertussis strains isolated in Russia in 2014–2020. The studied B. pertussis strains exhibit a homozygous phenotype for macrolide resistance.